Genetic Diversity of Captive and Wild Threatened Catfish Pseudoplatystoma corruscans in the São Francisco River - Dantas, Hozana Leite; dos Santos Neto, Miguel Arcanjo; Oliveira, Karine Kelly Cavalcanti; Severi, William; Diniz, Fábio Mendonça; Coimbra, Maria Raquel Moura (Reviews in fisheries science, 2013)
A genetic analysis was conducted of the critically endangered migratory catfish Pseudoplatystoma corruscans from the São Francisco River basin, the basin with the second highest hydropower capacity installed in Brazil. The analysis was conducted using five microsatellite markers previously described in the literature. Genetic diversity was analyzed and compared in three wild populations and a captive broodstock for a restocking program. Catfish populations of this river showed high genetic diversity in terms of heterozygosities; however, only half of the total number of alleles found in other basins were detected. Seven private alleles occurred in this basin and most of them at low frequencies, indicating they are under threat of extinction. Overall F ST and assignment test suggested low differentiation among the three wild populations; however, a marked distinction between these populations and the captive broodstock was observed. The number of alleles and low average relatedness estimates found for the captive population suggest that it could be used for restocking in areas where the wild population has collapsed, but should not be used for stock enhancement in areas where the wild population is extant. These results are important as a reference for genetic aspects that should be considered in fish management activities.